PENGARUH KEPUASAN DAN CITRA MALL PARAGON SORONG TERHADAP LOYALITAS PELANGGAN DI KOTA SORONG PROVINSI PAPUA BARAT DAYA - Maurits Flourance Noya; Mervin Komber; Pahmi Pahmi; Amiruddin Amiruddin (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the influence of Mall Paragon Sorong's image and customer satisfaction on customer loyalty, both partially and simultaneously. The background of this research is the intense competition in the retail industry in developing cities such as Sorong and the theoretical gap regarding the relationship between image, satisfaction, and loyalty in the context of modern shopping centers in Eastern Indonesia. This study employs a quantitative approach with a survey method. The research population consists of all visitors to Mall Paragon Sorong who have shopped at least twice. The sample was determined to be 100 respondents using the Hair et al. formula (number of indicators multiplied by 5-10). Data collection techniques used questionnaires with a 1-4 Likert scale. Data analysis included validity tests, reliability tests, multiple regression analysis, t-test (partial), F-test (simultaneous), and coefficient of determination (R²). The results showed that: (1) customer satisfaction has a significant influence on customer loyalty with a significance value of 0.000 (<0.05) and a regression coefficient of 0.476; (2) mall image does not have a significant influence on customer loyalty with a significance value of 0.503 (>0.05) and a regression coefficient of 0.044; (3) simultaneously, customer satisfaction and mall image have a significant influence on customer loyalty with an F-value of 20.167 and a significance of 0.000 (<0.05). The coefficient of determination (R²) value of 0.294 indicates that 29.4% of the variation in customer loyalty can be explained by customer satisfaction and mall image, while the remaining 70.6% is explained by other variables outside the study. The conclusion of this study is that customer satisfaction is the dominant factor influencing loyalty at Mall Paragon Sorong, while mall image has no direct influence. The recommendation for mall management is to prioritize improving visitor satisfaction through better service quality, facilities, and shopping experience.